TEACHING NUMBERS, COLOURS, END BASIC CONCEPTS THROUGH ENGLISH GAMES AND ACTIVITIES - Abduvoxidova Feruza Yo‘lchi qizi,; Mukhabbat Anatolevna Yusupova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper examines effective methods of teaching numbers, colours, and basic concepts  to  young  learners  through  English  games  and  interactive  activities.  The research is based on modern pedagogical theories such as communicative language teaching and constructivist approaches. The findings show that game-based learning significantly improves students' motivation, participation, and vocabulary retention.